Isolation of MA-ACS Gene Family and Expression Study of MA-ACS1 Gene in Musa acuminata Cultivar Pisang Ambon Lumut - LISTYA UTAMI KARMAWAN; SONY SUHANDONO; FENNY MARTHA DWIVANY (Bogor Agricultural University, Indonesia, 2009)
Musa acuminata cultivar pisang ambon lumut is a native climacteric fruit from Indonesia. Climacteric fruit ripening process is triggered by the gaseous plant hormone ethylene. The rate limiting enzyme involved in ethylene biosynthesis is ACC synthase (ACS) which is encoded by ACS gene family. The objective of this study is to identify MA-ACS gene family in M. acuminata cultivar pisang ambon lumut and to study the MA-ACS1 gene expression. The result showed that there were nine M. acuminata ACS gene family members called MA-ACS1–9. Two of them (MA-ACS1 and MA-ACS2) were assessed using reverse transcriptase PCR (RT-PCR) for gene expression study and it was only MA-ACS1 correlated with fruit ripening. The MA-ACS1 gene fragment has been successfully isolated and characterized and it has three introns, four exons, and one stop codon. It also shows highest homology with MACS1 gene from M. acuminata cultivar Hsian Jien Chiao (GenBank accession number AF056164). Expression analysis of MA-ACS1 using quantitative PCR (qPCR) showed that MA-ACS1 gene expression increased significantly in the third day, reached maximum at the fifth day, and then decreased in the seventh day after harvesting. The qPCR expression analysis result correlated with the result of physical analysis during fruit ripening. Key words: pisang ambon lumut, MA-ACS gene family, gene characterization, gene expression, quantitative PCR (qPCR)